PELATIHAN PENGUMANDANGAN ADZAN DAN IQOMAH DI TAMANPENDIDIKANAL-QUR’ANMASJID AROFAH, DUSUN BANDUNG DAN DUSUN SONGBANYU 1,KECAMATAN SONGBANYU,GUNUNG KIDUL, DAERAH ISTIMEWA YOGYAKARTA - Muntoha Muntoha (UII, 2015)
Adzan is a perfect da’wah sentence whose content is dominated by the phrase ofunity and equipped with the teachings of prayers and invitations to achieve greatness inthe world and the afterlife. And iqamah is a call notice to the audience (pilgrims) to beprepared to stand praying, with the wording that has been determined by the syara '. Thecall to prayer and iqamah very important for muslim. In addition to the call to prayerechoed as a sign of prayer time has come and iqamah as a sign that the prayer is about tobegin, at certain times also call for prayer and iqamah echoed. Thus the importance of thecall to prayer and iqamah, the echoed should not be done incorrectly. The echoing learningof adzan and iqamah should be carried out continuously. Noting this, authors took theinitiative to provide an echoung learning of adzan and iqamah correctly for children inDusun Bandung and Dusun Songbanyu 1. It is also based on the absence of muezzinregeneration in those two hamlet. With hope, besides they can echo adzan and iqamahcorrectly, they also become closer to Allah SWT.